Effect of the COVID-19 detraining on athletes` psychological health - Nakisa, N.; Rahbardar, M. G. (Asian Journal of Sports Medicine, 2021)
In the current study, the team tried to shed light on the probable results of the coronavirus detraining on athletes` psychological health and encourage coaches and owners of the teams to pursue appropriate interventions to reduce the unfavorable effects of detraining on the athletes.